243. Performance comparison of head RF multicoil array: What are the advantages of increasing coil numbers?. (December 2018) - Mascaro, L.; Ambrosi, C.; Pinardi, C.; Belligotti, E.; Moretti, R.; Forcella, F.G.; Gasparotti, R.
Abstract : Purpose: RF Multi-coil arrays is a well known MRI technology aimed at increasing signal to noise ratio (SNR) over large volumes. However when the coil number increase and coil elements become very small there is a lack of combined signal uniformity, particularly for the head coils, and the real benefit should be evaluated. This work compares quantitatively a 20 and 64 RX head multicoil array performance both for phantoms and in vivo measurements. Methods: Measurements were performed on 3T Siemens Skyra system. A spherical homogeneous phantom was scanned with both RX coils using a high resolution T1-3D-MPrage protocol optimized for in vivo morphological studies and repeated with different acceleration factors (AF from 0 to 8). Phantom volumes were analyzed offline with a bespoke imagej plugin that calculates quality indices, such as SNR and Normalized Absolute Average Difference (NAAD), over the entire volume, extending to 3D the standard 2D evaluation proposed by NEMA. The same acquisitions were performed in vivo, scanning 10 healthy volunteers and analyzing data offline in terms of SNR of small sub-cortical tissues located in the central brain volumes, where the worst coil performance is expected. Results: Results from phantom measurements showed no significant differences, in terms of uniformity, for the coils performance. NAAD didn't change with acceleration factor (NAAD = 0, 84). SNR (see Fig. 1) is about the same for unaccelerated and AF = 8 images, these last due to the very low SNR values, but it becomes higher for 64ch coil with AF = 2, 4, 6, due to a lower noise increase rate. In vivo measurements present a significant difference between SNR from the two coils, with better performances of the 64ch coil for all the segmented tissues when an AF of 4 and 6 is used and for some of the segmented tissues with AF = 2. Conclusions: increasing coil numbers can be useful in morphological protocols only when high acceleration factors, up to 6, are used.